Pendampingan Pembelajaran dalam Pengkondisian Siswa melalui Ice Breaking - Tholib Hariono; Hilyah Ashoumi; Anggi Septa Mujahadah; Adriansyah Adransyah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The objectives of this mentoring activity include; Increase students' understanding of religious knowledge, so that they are able to develop themselves in line with religious norms and are able to practice them in the development of science, Growing and developing Islamic sciences in integrating relationships with Allah SWT, Apostles, humans, the universe and even with themselves Provide deep understanding to students about religious teachings and how to implement them in daily life, Provide insight to students/students to behave in daily life Islamically, Develop and create talents of students/students in the field of religious education, especially about reading and writing Al-Qur'an. The methods used include; lecture and discussion methods. The results of this activity In the implementation of learning training activities carried out at TPQ Al-Misbah Banjarsari Village, there are several inhibiting factors in learning activities carried out at TPQ AL-Misbah, namely: Lack of cooperation between managers, teachers and students, Lack of willingness common from students / students to take part in learning, teaching time is relatively short, class management is monotonous. With these obstacles, there are several ways to motivate the spirit of learning at TPQ Al-Misbah, namely: The existence of cooperation between managers, teachers and students/students, Varied learning methods that are more cheerful and conveyed, Adding learning time.